PNKP deficiency mimicking a benign hereditary chorea: The misleading presentation of a neurodegenerative disorder. (July 2019) - Caputi, C.; Tolve, M.; Galosi, S.; Inghilleri, M.; Carducci, C.; Angeloni, A.; Leuzzi, V.
Abstract: PNKP gene encodes for a kinase/phosphatase involved in DNA damage response, controlled and stabilized by ATM phosphorylation. PNKP deficiency, thus far described in 40 subjects, has been associated with a complex neurological phenotype encompassing microcephaly, seizures, developmental delay, ataxia, oculomotor apraxia and polyneuropathy. We report a new case expanding the clinical phenotype of this rare disorder. This 25 years old girl presented with chorea at the age of 2 years and remained stable up to the adult age when the emergence of fatigability and asthenia of lower limbs prompted a new examination disclosing a sensory-motor axonal demyelinating neuropathy. Clinical exome sequencing revealed two previously described variants in PNKP gene. This case highlights the phenotypic variability of PNKP associated disorders, showing that an early onset apparently non progressive chorea can be the presenting symptoms of this rare condition.